2021
DOI: 10.1002/pro.4042
|View full text |Cite
|
Sign up to set email alerts
|

The leucine zipper EF‐hand containing transmembrane protein‐1 EF‐hand is a tripartite calcium, temperature, and pH sensor

Abstract: Leucine Zipper EF‐hand containing transmembrane protein‐1 (LETM1) is an inner mitochondrial membrane protein that mediates mitochondrial calcium (Ca2+)/proton exchange. The matrix residing carboxyl (C)‐terminal domain contains a sequence identifiable EF‐hand motif (EF1) that is highly conserved among orthologues. Deletion of EF1 abrogates LETM1 mediated mitochondrial Ca2+ flux, highlighting the requirement of EF1 for LETM1 function. To understand the mechanistic role of this EF‐hand in LETM1 function, we chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 62 publications
(165 reference statements)
2
8
0
Order By: Relevance
“…This pKa and fully solvent-exposed location within the short linker, suggest a mechanism for the robust structural and biophysical attribute sensitivity of the domain to pH changes in the 6.0-8.0 range. Indeed, as previously reported (Lin et al, 2021), we found apo WT pH 6.0 showed significantly greater negative ellipticity at ~222 nm (i.e. more -helicity) compared to apo WT at pH 7.8; moreover, no such pH-dependent difference was observed for holo WT, likely because of the increased -helicity mediated by Ca 2+ binding (Figure 7b and Table 2).…”
Section: His662 Is Responsible For Ph-dependent Regulation Of Ca 2+ S...supporting
confidence: 87%
See 2 more Smart Citations
“…This pKa and fully solvent-exposed location within the short linker, suggest a mechanism for the robust structural and biophysical attribute sensitivity of the domain to pH changes in the 6.0-8.0 range. Indeed, as previously reported (Lin et al, 2021), we found apo WT pH 6.0 showed significantly greater negative ellipticity at ~222 nm (i.e. more -helicity) compared to apo WT at pH 7.8; moreover, no such pH-dependent difference was observed for holo WT, likely because of the increased -helicity mediated by Ca 2+ binding (Figure 7b and Table 2).…”
Section: His662 Is Responsible For Ph-dependent Regulation Of Ca 2+ S...supporting
confidence: 87%
“…Sequence comparison of the 12-residue loop shows strong conservation with other canonical EF-hand loop sequences such as calmodulin EF2 (CaM), parvalbumin EF3 and calbindin D9k EF2 with the exception of the Asp residue at the 12 th position, which commonly confers Mg 2+ binding affinity to non-canonical EF-hands (Figure 1b) (Tan et al , 2022; Yanyi et al , 2010). Nevertheless, our previous research indicates that the LETM1 EF-hand selectively binds Ca 2+ (Lin et al ., 2021), which is consistent with the high sequence conservation at the other liganding loop residue positions when compared to ∼1,700 canonical Ca 2+ binding loops (Figure 1c) (Sigrist et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this transporter has been a topic of controversy, the mitochondrial Ca 2+ /H + exchanger is most probably encoded by LETM1 [ 80 , 81 ]. LETM1 appears to directly sense both H + and Ca 2+ [ 82 ] and to play transport-unrelated roles in signaling, including its physical anchoring to the mitochondrial ribosome protein L36 [ 83 ]. The nature of the mitochondrial Na + /H + exchanger (NHE) is also controversial.…”
Section: Interdependent Ion Fluxes Drive Mitochondrial Functionmentioning
confidence: 99%
“…Re-expression of an shRNA-resistant variant of wild-type Letm1 in Letm1 KD neurons rescued mitochondrial Ca 2+ efflux rates, validating the specificity of the Letm1 shRNA (Figure 1F). Letm1 presents a Ca 2+ binding EF-hand domain oriented towards the mitochondrial matrix 46,47 (Figure 1A). We hypothesized that such a domain would be ideally positioned to activate Letm1 during neurotransmission, as it could sense mitochondrial Ca 2+ increases during firing.…”
Section: Resultsmentioning
confidence: 99%